Facilitators and obstacles to the inclusion of sports in Chile (Revista horizonte, 2021)
The research describes the factors that hinder or favor the practice of sports for people with disabilities in the regional selections of Goalball, Rugby in saddle and wheelchair basketball in the ninth region of Araucanía. The  methodology  used  correspondsto  the  qualitative  one  and  the  main  data  collection  technique  was  the semi-structured  interview.  The  participants  in  this  study  were;  19  athletes,  5  teachers,  and  3  parents  whose children  have  physical  disabilities,  and  are  part  of  the  rugby,  goalball  andbasketball  teams  of  the  Temuco district  of  Chile.  The  main  findings  reveal  that  the  main  obstacle  to  the  practice  of  sports  for  people  with disabilities  is  the  lack  of  resources,  in  addition,  a  finding  that  is  typical  of  this  research  shows  us  that  the climate  as  an  intervening  element  of  the  regional  geographical  reality  hinders  the  practice  of  sports,  as  the main  facilitator,  the  motivation  of  the  practitioners  is  stated,  finally,  it  is  stated  that  the  main  challenge  is linked to the dissemination of inclusive sports that generate awareness among the population, about the fact that people with disabilities are rare, but , normal.